(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article examines the methodology and current practices in assessing the corporate governance levels of joint-stock companies in Uzbekistan, with a specific focus on international ratings. As the Uzbek economy continues to evolve, enhancing corporate governance is crucial for attracting foreign investment and fostering sustainable development. The article outlines the key indicators used in corporate governance assessments, including board structure, shareholder rights, and disclosure practices. It also highlights recent trends, such as the adoption of best practices, regulatory reforms, and the increasing importance of transparency and compliance with international standards. By adopting modern governance methodologies and integrating technology, Uzbek companies can improve their governance ratings and overall business operations. This study emphasizes the necessity of education and stakeholder engagement to overcome existing challenges in corporate governance and promote a robust governance framework.